Social Dysfunction in Psychosis Is More Than a Matter of Misperception: Advances From the Study of Metacognition - Lysaker, Paul H.; Hasson-Ohayon, Ilanit; Wiesepape, Courtney; Huling, Kelsey; Musselman, Aubrie; Lysaker, John T. (Frontiers in Psychology, 2021)
Many with psychosis experience substantial difficulties forming and maintaining social bonds and report persistent social alienation and a lack of a sense of membership in a larger community. While it is clear that social impairments in psychosis cannot be fully explained by symptoms or other traditional features of psychosis, the antecedents of disturbances in social function remain unknown. One recent model has proposed that deficits in social cognition may be a root cause of social dysfunction. In this model social relationships may become untenable among persons diagnosed with psychosis when deficits in social cognition result in inaccurate ideas of what others feel, think or desire. While there is evidence to support the influence of social cognition upon social function there are substantial limitations to this point of view. Many with psychosis have social impairments but not significant deficits in social cognition. First person and clinical accounts of the phenomenology of psychosis also do not match this model. Persons with psychosis do not report the experience of making mistakes when trying to understand others. They report that intersubjectivity, which involves more than the correct apprehension of others, has become extraordinarily difficult. In this paper we therefore explore how research in metacognition in psychosis might transcend these limitations and address some of the ways in which intersubjectivity and more broadly social function is compromised in psychosis. Specifically, this paper will first review research on the relationship between social cognitive abilities and social function in psychosis, including measurement strategies and limits to its explanatory power, particularly regarding its account for alterations in intersubjectivity. Next, we present research on the integrated model of metacognition in psychosis and its relation to social function. We then discuss how this model might go beyond social cognitive models of social dysfunction in psychosis by describing how compromises in intersubjectivity occur as metacognitive deficits leave persons without an integrated sense of others’ purposes, places in the world, possibilities and personal complexities. Implications for the development of clinical interventions will finally be explored.